Starting a Farmers’ Market - Mickie E. Swisher; James Sterns; Jennifer Gove (EDIS)
There are many details that separate great farmers’ markets from struggling or mediocre markets. This publication discusses eight of the most important steps to consider as you start a farmers’ market in your community. Also included are Useful Facts about Farmers’ Markets, legal information, an example of bylaws and rules for a farmers’ market and links to farmers’ markets online. This document is FCS5257-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: August 2003.